WAYS TO USE MARKETING INFORMATION IN THE PROCESS OF EVALUATING THE ENTERPRISE - Musayeva Shoira Azimovna; Usmonova Dilfuza Ilkhomovna; Usmanov Farzod Shokhrukhovich (Scholar Express Journals, 2022)
This article considers the assessment of the competitiveness of the enterprise by the type of market, competitors producing substitute goods, analysis, product quality, prices, sales channels, advertising, as well as a list of major importers of these goods in the country.
Keywords: Enterprise; business; brand; quality; sales; advertising; information